2015
DOI: 10.3109/08958378.2015.1104402
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in DNA methylation and airway hyperreactivity in response toin uteroexposure to environmental tobacco smoke

Abstract: Growing evidence indicates that prenatal exposure to maternal smoking is a risk factor for the development of asthma in children. However, the effects of prenatal environmental tobacco smoke (ETS) exposure on the genome and lung immune cells are unclear. This study aims to determine whether in utero ETS exposure alters DNA methylation patterns and increases airway hyperreactivity (AHR) and inflammation. Pregnant C57BL/6 mice were exposed daily to a concentration of 1.0 mg/m3 ETS. AHR was determined in the 6-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
3
20
0
1
Order By: Relevance
“…Epigenetic changes may account for such generational effects [71]. Mice models show alterations in DNA methylation and airway hyperreactivity in response to in utero ETS [72]. Recent human studies have also found smoke-exposure-specific blood DNA methylation changes present in preschool children, which were comparable to those found at birth [73].…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic changes may account for such generational effects [71]. Mice models show alterations in DNA methylation and airway hyperreactivity in response to in utero ETS [72]. Recent human studies have also found smoke-exposure-specific blood DNA methylation changes present in preschool children, which were comparable to those found at birth [73].…”
Section: Resultsmentioning
confidence: 99%
“…We believe these associations are gene specific as there is substantial evidence that epigenetic regulation of both FOXP3 and IFNγ is associated with clinically relevant outcomes (Liu, Ballaney et al 2008, Brand, Kesper et al 2012, Kohli, Garcia et al 2012, Niedzwiecki, Zhu et al 2012, Runyon, Cachola et al 2012, Tang, Levin et al 2012). There is more limited evidence to suggest that differences in global methylation instead may explain outcomes related to exposure to cigarettes and air pollution (Breton, Byun et al 2009, Lee, Jaffar et al 2015, Breton, Yao et al 2016) and allergic sensitization(Sordillo, Lange et al 2013) in some, but not other (Chi, Liu et al 2016), studies.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported altered global and gene-specific methylation in 6-week old mice exposed to prenatal ETS that corresponded with alterations in pulmonary inflammation and airway hyperreactivity, suggesting that prenatal ETS exposure can increase disease susceptibility through altered DNA methylation (Lee et al, 2015). However, whether the epigenetic effects of these exposures resolve with age and to what extent these effects may alter the mechanisms involved in adult onset lung pathologies remained unaddressed.…”
Section: Introductionmentioning
confidence: 84%
“…Breeding and ETS exposure were conducted as previously described (Lee et al, 2015; Brown et al, 2016). Briefly, two female mice were paired with one male mouse to create a timed-pregnant exposure scenario.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation